Business without boundaries : - Mankin, Donald A. (Jossey-Bass, 2004)
This book explores a number of wide-ranging, real world cases that identify hands-on principles for successful collaboration. It contains steps for creating, facilitating, and supporting complex collaborations throughout the organization and beyond. They will learn how to "team" across boundaries in the new global economy. The recommendations are specific enough to apply to particular forms of complex collaboration (e.g. virtual teams, inter-organizational alliances), but general enough to apply to new forms that have yet to emerge.